Polycystic ovary syndrome and risk factors for gestational diabetes - Sanna Mustaniemi; Marja Vääräsmäki; Johan G. Eriksson; Mika Gissler; Hannele Laivuori; Hilkka Ijäs; Aini Bloigu; Eero Kajantie; Laure Morin‐Papunen (2018)
To study the roles of self-reported symptoms and/or prior diagnosis of polycystic ovary syndrome (PCOS) and other potential risk factors for gestational diabetes mellitus (GDM) and to clarify whether the screening of GDM in early pregnancy is beneficial for all women with PCOS.The FinnGeDi multicentre case-control study including 1146 women with singleton pregnancies diagnosed with GDM and 1066 non-diabetic pregnant women. There were 174 women with PCOS (symptoms and/or diagnosis self-reported by a questionnaire) and 1767 women without PCOS (data missing for 271).The study population (N = 1941) was divided into four subgroups: GDM + PCOS (N = 105), GDM + non-PCOS (N = 909), non-GDM + PCOS (N = 69), and controls (N = 858). The participants' characteristics and their parents' medical histories were compared.The prevalence of PCOS was 10.4% among GDM women and 7.4% among non-diabetics (odds ratios (OR) 1.44, 95% CI: 1.05-1.97), but PCOS was not an independent risk for GDM after adjustments for participants' age and pre-pregnancy BMI (OR 1.07, 95% CI: 0.74-1.54). In a multivariate logistic regression analysis, the most significant parameters associated with GDM were overweight, obesity, age ≥35 years, participant's mother's history of GDM, either parent's history of type 2 diabetes (T2D) and participant's own preterm birth.The increased risk of GDM in women with PCOS was related to obesity and increased maternal age rather than to PCOS itself, suggesting that routine early screening of GDM in PCOS women without other risk factors should be reconsidered. Instead, family history of GDM/T2D and own preterm birth were independent risk factors for GDM.